Performance of Western Hemisphere Trading Blocs : A Cost-Corrected Gravity Approach - Croce, Enzo (IMF Working Papers; Working Paper, 2004)
We study the performance of the four Western Hemisphere trading blocs during the period 1978-2001. For the North American Free Trade Agreement (NAFTA), trade integration outweighed trade diversion; for MERCOSUR, increased integration and trade diversion went hand in hand; for the Central American Common Market (CACM) and the Andean Community, the evidence points to trade diversion only. We also find that trade among neighboring countries has increased since the early 1990s. The estimations are based on a nonlinear gravity equation that incorporates the hypothesis that exports create externalities that affect trade costs. This hypothesis might help reconcile the theoretical unitary income elasticity with most empirical findings of a non-unitary income elasticity in studies using the gravity equation.